2018
DOI: 10.1002/2017wr021127
|View full text |Cite
|
Sign up to set email alerts
|

Three‐Dimensional Effects of Artificial Mixing in a Shallow Drinking‐Water Reservoir

Abstract: Studies that examine the effects of artificial mixing for water‐quality mitigation in lakes and reservoirs often view a water column with a one‐dimensional (1‐D) perspective (e.g., homogenized epilimnetic and hypolimnetic layers). Artificial mixing in natural water bodies, however, is inherently three dimensional (3‐D). Using a 3‐D approach experimentally and numerically, the present study visualizes thermal structure and analyzes constituent transport under the influence of artificial mixing in a shallow drin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
17
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1
1

Relationship

2
5

Authors

Journals

citations
Cited by 18 publications
(18 citation statements)
references
References 38 publications
1
17
0
Order By: Relevance
“…We applied and evaluated FLARE at Falling Creek Reservoir (FCR), a dimictic, eutrophic reservoir located in Vinton, Virginia, USA (37.30°N,79.84°W). FCR is a shallow (maximum depth=9.3 m, mean depth=4 m), small (surface area=0.119 km 2 ) reservoir [ Chen et al 2018 ]. The lake exhibits summer thermal stratification from May to October and is ice-covered from January to February or March [ Carey et al 2019c ].…”
Section: Methodsmentioning
confidence: 99%
“…We applied and evaluated FLARE at Falling Creek Reservoir (FCR), a dimictic, eutrophic reservoir located in Vinton, Virginia, USA (37.30°N,79.84°W). FCR is a shallow (maximum depth=9.3 m, mean depth=4 m), small (surface area=0.119 km 2 ) reservoir [ Chen et al 2018 ]. The lake exhibits summer thermal stratification from May to October and is ice-covered from January to February or March [ Carey et al 2019c ].…”
Section: Methodsmentioning
confidence: 99%
“…This possibility is supported by 3-D hydrodynamic modeling of the same reservoir by Chen et al (2018). Using field turbidity data, Chen et al (2018) found that the intensity of EM operation in FCR was an important driver of short-term particle transport, and that mixing facilitates the transport of particulate matter from the shallow upstream region to the deep lacustrine region in the reservoir [26]. The increased turbidity at the deepest site in FCR after the first mixing event coincided with an increase in volume-weighted TP throughout the treatment zone, as well as an increase in volume-weighted green algae, cyanobacteria, and cryptophyte biomass and total phytoplankton biomass in the treatment zone of FCR.…”
Section: Discussionmentioning
confidence: 77%
“…As shown in Figure 9, the increase in turbidity at the deepest site in FCR after EM1 likely originated in shallow, turbid upstream regions of the reservoir and was subsequently entrained downstream over the course of the week post-EM1. This possibility is supported by 3-D hydrodynamic modeling of the same reservoir by Chen et al (2018). Using field turbidity data, Chen et al (2018) found that the intensity of EM operation in FCR was an important driver of short-term particle transport, and that mixing facilitates the transport of particulate matter from the shallow upstream region to the deep lacustrine region in the reservoir [26].…”
Section: Discussionmentioning
confidence: 88%
See 2 more Smart Citations